Systematic Review - State of the Art: strategies for vigor evaluation and production of high-vigor soybean seeds - Andreza Cerioni Belniaki; Mayla Daiane Correa Molinari; Fernando Augusto Henning; Maristela Panobianco (Journal of Seed Science, 2022)
Abstract: A systematic approach was employed with the objective of compiling updated and more promising information on the quality of soybean seeds, traits, treatments and analysis techniques. Among the 6,899 academic materials retrieved between 2017 and 2022, 57 of them were included in the study, separated into three groups: Group 1 - Theoretical materials addressing traits related to seed vigor, which can be used in biotechnological strategies and improvement of different species; Group 2 - Practical materials that apply techniques of treatment of soybean seeds; and Group 3 - Practical materials that apply techniques to evaluate vigor in soybean seeds. From the approach used, it was possible to observe that several genes, proteins and QTLs are associated with seed vigor. Seed treatment techniques focus on the use of biological and physical products, but there is a lack of studies validating these benefits in the field. Among the methods for evaluating the vigor of soybean seeds, the techniques of image analysis (visible light, LIBS, NIR, FTIR, FT-NIR, HSI-NIR, FHSI, Hyperspectral, Fluorescence spectral) and the use of software (Vigor-S®, SVIS®, SAPL®, IJCropSeed, Ilastik, VideometerLab®, MATLAB, ENVI®) stand out.